OPTIMALISASI PEMANFAATAN SARANA PRASARANA DALAM UPAYA UNTUK MENINGKATKAN MUTU PENDIDIKAN (STUDI MULTISITUS) DI UPT SDN KEBONHARJO 1 DAN UPT SDN DINGIL 1 KECAMATAN JATIROGO KABUPATEN TUBAN - Mochamad Maksum; Taufiq Harris; Suyitno (STKIP Subang, 2026)
This research is motivated by the importance of facilities and infrastructure as key components of school management for enhancing learning quality and educational standards, particularly in rural areas that often face physical facility limitations. The study aims to analyze the adequacy of facilities and infrastructure, budget efficiency, and user satisfaction at UPT SDN Kebonharjo 1 and UPT SDN Dingil 1 in Jatirogo District, Tuban Regency. Employing a qualitative approach with a multi-site study design, data collection was conducted through in-depth interviews, participant observation, and document analysis. Data analysis utilized inductive and cross-site comparative methods, with validity verified through qualitative validation tests. The research findings indicate the following: Facilities and Infrastructure Adequacy: Despite limitations at the basic functional level, both schools managed to fulfill essential learning rights by providing six adequate classrooms. UPT SDN Kebonharjo 1 achieved a 1:1 textbook ratio, while UPT SDN Dingil 1 focused on the adequacy of classroom furniture. Budget Efficiency: Efficiency was achieved by prioritizing the periodic maintenance of existing assets to minimize procurement costs. Spatial constraints were addressed cost-effectively by reconfiguring the schoolyard into a multifunctional (shared-space) area and implementing flexible scheduling. User Satisfaction: Teachers and students expressed satisfaction and a strong sense of comfort in the learning environment. The schools also successfully expanded their educational ecosystem through strategic, no-cost partnerships with the local Community Health Center (Puskesmas), the Regional Library, and the Quran Education Center (TPQ). Furthermore, the physical limitations at UPT SDN Kebonharjo 1 served as the basis for *Dapodik* (Basic Education Data) administration to formulate a master plan for a new building proposal on a 2,050 m² site. Keywords: Optimization, Infrastructure, Educational Quality, Multi-Site Study